HUBUNGAN TINGKAT PENGETAHUAN PENGUNJUNG TENTANG MENCUCI TANGAN DENGAN PERILAKU MENCUCI TANGAN DI RUANG INTENSIVE CARE UNIT (ICU) RSUD MERAUKE - Ardhanari Hendra Kusuma (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Background: Hospital as a place to treat sick people, hospitals are breeding grounds for germs and prone to transmission of nosocomial infections. Visitors can be contaminated with germs from the hospital environment or visitors can become carriers that spread germs to patients and the hospital environment. Hand washing is an effective enough way to prevent the spread of infection and protect patients from infection. Research Objectives: To determine the relationship between workload and stress on nurses in the ICU room at Merauke Hospital. Research Method: Knowing the relationship between the level of knowledge of visitors about hand washing and hand washing behavior in the ICU. Research method: research design using descriptive analysis with a cross sectional approach. The study population was all patient visitors in the ICU room of Merauke Hospital with a total sample of 46 visitors using accidental sampling technique. The research measurement tool used a questionnaire using univariate data analysis using frequency distribution and bivariate data analysis using the Fisher Exact test. Research results: Most respondents (73.9%) had a high level of knowledge and more than half of respondents (71.7%) indicated good hand washing behavior. Data analysis using the Fisher Exact test found that there was a relationship between the level of knowledge and visitor hand washing behavior (p=0.001; OR=0.86; α=0.05). Conclusion: The results of this study prove that the level of knowledge has a positive relationship with visiting behavior at Merauke Hospital.